IL-27-containing exosomes secreted by innate B-1a cells suppress and ameliorate uveitis - Kang, Minkyung; Yadav, Manoj Kumar; Mbanefo, Evaristus C.; Yu, Cheng-Rong; Egwuagu, Charles E. (Frontiers in Immunology, 2023)
IL-27 is a heterodimeric cytokine composed of Ebi3 and IL-27p28 and can exert proinflammatory or immune suppressive effects depending on the physiological context. Ebi3 does not contain membrane-anchoring motifs, suggesting that it is a secreted protein while IL-27p28 is poorly secreted. How IL-27p28 and Ebi3 dimerize in-vivo to form biologically active IL-27 is unknown and major impediment to clinical use of IL-27 derives from difficulty of determining exact amount of bioavailable heterodimeric IL-27 needed for therapy. To better understand potential mechanisms by which IL-27 mediates immune suppression we characterized an innate IL-27-producing B-1a regulatory B cell population (i27-Breg) that suppress neuroinflammation in mouse models of multiple sclerosis and uveitis. Contrary to prevailing view that IL-27 is a soluble cytokine, we show that i27-Breg cells express membrane-bound IL-27. Immunohistochemical and confocal analyses revealed that IL-27p28 is a transmembrane protein in B cells and we co-localized expression of p28 and Ebi3 in association with CD81 tetraspanin, a BCR-coreceptor protein, to the plasma membrane. Most surprisingly, we found that i27-Breg cells secrete IL-27-containing exosomes (i27-exosomes) and adoptive transfer of the i27-exosomes suppressed uveitis in mice by antagonizing Th1/Th17 responses, upregulating inhibitory-receptors associated with T-cell exhaustion, while inducing Treg expansion. Use of i27-exosomes thus obviates the IL-27 dosing problem, making it possible to determine bioavailable heterodimeric IL-27 needed for therapy. Moreover, as exosomes readily cross the blood-retina-barrier and no adverse effects were observed in mice treated with i27-exosome, results of this study suggest that i27-exosomes might be a promising therapeutic approach for CNS autoimmune diseases.